SINDROM METABOLIK DENGAN RIWAYAT KONSUMSI ALKOHOL MENINGKATKAN RISIKO TERJADINYA CHRONIC KIDNEY DISEASE: STUDI KASUS KONTROL DI RS PANTI NIRMALA KOTA MALANG - Ariyanti, Rea (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
Chronic Kidney Disease (CKD) is a global public health problem with a high prevalence and incidence of kidney failure, poor prognosis, and has a large impact on morbidity, mortality, and socioeconomics of the community due to high treatment costs. Globally, CKD is the 12th leading cause of mortality and 17th for morbidity. There are several risk factors that are thought to increase the incidence of CKD, one of which is Metabolic Syndrome (SM). This study aims to determine the relationship between SM and the incidence of CKD at Panti Nirmala Hospital in Malang. The research design is case-control. The sample was 146 respondents, consisting of 73 case groups and 73 control groups. Data analysis using logistic regression. In the CKD group, the percentage of respondents with SM was 53.4% while in the group that did not suffer from CKD, the percentage of respondents with DM was 21.9%. It is known that after controlling for gender and age, respondents who have a history of consuming alcohol have an 11.9 times higher chance of developing CKD than respondents who do not have SM. It is recommended for the public to have regular health checks and change a healthy lifestyle, avoid consuming alcohol, and carry out regular health checks such as measuring blood pressure and blood sugar.